Current trends in topical therapies for chronic rhinosinusitis: update and literature review. (1st February 2017) - Varshney, Rickul; Lee, Jivianne T.
ABSTRACT: Introduction: Chronic rhinosinusitis (CRS) affects millions of patients worldwide. The disease is multifactorial with influences including anatomic factors, immunological disturbances, and altered sinonasal microbiome. Although oral medications are effective in controlling some symptoms, they are associated with side effects and long-term use is not ideal. Thus, topical therapies have emerged as an alternative delivery method for localized, high-concentration medication with less side effects. Areas covered: This is a review of the various topical therapies available or under investigation for the management of CRS. Common medications such as saline, steroids, and antimicrobials will be discussed. Furthermore, additives including manuka honey, xylitol, surfactant, N-chlorotaurine, Dead Sea salt, and sodium hyaluronate will be addressed. Innovations in topical therapies, such as drug-eluting biomaterials and photodynamic therapy, will also be reviewed. Expert opinion: Although topical therapies provide a high dose of active substance at the site of disease, their efficacy in CRS is not clear. Topical saline and intranasal steroids appear to consistently demonstrate therapeutic benefits. However, other topical medications require further investigation to determine long-term clinical efficacy and safety. A better understanding of their effects on the sinonasal mucociliary system is needed before they become the standard of care in CRS.